The Effectiveness of Family Psychoeducation to Manage the Mood of Patients with Bipolar Disorder: A Systematic Review - Yusuf, Ah.; Rachmawati, Suhardiana (International Journal of Psychosocial Rehabilitation, 2020)
Psychoeducational interventions for both the family and patients with bipolar disorder are effective at improving compliance and preventing relapse. Whether there is a benefit from these interventions on the management of the mood of bipolar disorder patients has been little explored. This systematic review has investigated the effectiveness of psycho-education on the family care outcome related to the management of mood symptoms with bipolar disorder. We searched for Randomized Controlled Trials (RCTs) published in English across 2 databases. Fifteen RCTs were included and the intervention duration ranged from 6 to 96 weeks. The relevant articles published between 2008 and 2018 were obtained by searching Scopus and Science Direct. We looked into the effectiveness of family psychoeducation on the management of the mood of patients with bipolar disorder. Psychoeducation for the family also had some positive effects used to help the patients with bipolar disorder to increase the quality of their lives by developing their knowledge about bipolar disorder. This included information about the recurrence rate of the illness, the necessary medication and its adverse effects, triggering factors, the needed adherence to drugs, how to control the symptoms, stress management, the risk of suicide, the avoidance of the use of alcohol and the importance of leading a well- structured life.